2021
DOI: 10.3389/fcell.2021.784244
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Rescues in vitro Embryonic Development by Correcting Impaired Active DNA Demethylation

Abstract: During preimplantation development, a wave of genome-wide DNA demethylation occurs to acquire a hypomethylated genome of the blastocyst. As an essential epigenomic event, postfertilization DNA demethylation is critical to establish full developmental potential. Despite its importance, this process is prone to be disrupted due to environmental perturbations such as manipulation and culture of embryos during in vitro fertilization (IVF), and thus leading to epigenetic errors. However, since the first case of abe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…In line with this notion, DNA methylation and gene expression patterns of IVF embryos have been partially corrected by supplementing oviductal fluid into culture medium. Correspondingly, our previous study has found that AsA, enriched in both embryos and oviduct environment, is involved in DNA demethylation in preimplantation embryos 14 . Similarly, the present study identifies that GSH, which is also synthesized by both the embryo and oviduct, maintains redox homeostasis and safeguards DNA demethylation in preimplantation.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In line with this notion, DNA methylation and gene expression patterns of IVF embryos have been partially corrected by supplementing oviductal fluid into culture medium. Correspondingly, our previous study has found that AsA, enriched in both embryos and oviduct environment, is involved in DNA demethylation in preimplantation embryos 14 . Similarly, the present study identifies that GSH, which is also synthesized by both the embryo and oviduct, maintains redox homeostasis and safeguards DNA demethylation in preimplantation.…”
Section: Discussionsupporting
confidence: 82%
“…Correspondingly, our previous study has found that AsA, enriched in both embryos and oviduct environment, is involved in DNA demethylation in preimplantation embryos. 14 Similarly, the present study identifies that GSH, which is also synthesized by both the embryo and oviduct, maintains redox homeostasis and safeguards DNA demethylation in preimplantation. The important role of paracrine GSH in developmental potential was further supported by the result that exogenous that exogenous supplementation of GSH significantly prompted ICM specification via facilitating 5hmC formation.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…To decipher the receptor–ligand repertoire of embryonic WNT signaling, we first analyzed the dynamic expression patterns of WNT signaling receptors in in vivo conceived embryos and their temporally corresponding oviduct/uterus, using our previously published RNA-seq data [ 16 ]. Several WNT signaling receptors, such as Fzd5 , Fzd6 , etc., showed higher expression levels in oviduct/uterus, indicating that these receptors may function in the oviduct/uterus ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%